Coagulation parameters in hyperthyroid cats before and after radioiodine treatment compared with healthy controls. Issue 12 (December 2019) - Cui, Yi; Heuser, Katharina; Bauer, Natali; Neiger, Reto
Objectives: The aim of the study was to describe the coagulatory state of hyperthyroid cats before and after successful radioiodine therapy (RIT) compared with healthy age-matched controls, using classical coagulation parameters and thromboelastogram (TEG) as a global assessment method. The differences in coagulation activity after RIT, depending on the thyroid hormone (normal vs low total thyroxine [T4]) state, were also evaluated. Methods: Fifteen hyperthyroid cats and 10 healthy age-matched controls were recruited. Hyperthyroid cats that remained hyperthyroid 14 days after RIT were excluded. Haematology, biochemistry, T4, prothrombin time (PT), activated partial thromboplastin time (aPTT), fibrinogen and TEG were assessed in control cats and hyperthyroid cats before and 7 and 14 days after RIT. Two weeks after successful RIT, further comparisons were made between cats with normal T4 vs those with low T4. Results: Fourteen days after successful RIT, 7/15 cats had normal T4 and 8/15 had low T4. Thrombocytosis was noted in 6/15 cats after treatment. Fibrinogen was significantly higher ( P <0.001) and PT shorter ( P <0.01) in the hyperthyroid cats compared with the healthy controls and these changes persisted after RIT. Persistent increases in fibrinogen, PT, TEG maximal amplitude and TEG clot rigidity, reflecting clot stability, after RIT primarily occurred in the cats with normal T4. TEG-K (time until preset amplitude of 20 mm is reached) and alpha (α) angle reflected impaired fibrin cross-linking ability prior to RIT, which significantly increased after therapy ( P <0.05). Conclusions and relevance: Based on some of the coagulation parameters, cats with hyperthyroidism showed hypercoagulable tendencies, which were mildly increased after RIT, possibly due to transient radiation-induced thyroiditis.